Analisis Hukum Islam dan Undang – Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat terhadap Keabsahan Penggunaan QRIS sebagai Sarana Penghimpunan Dana Zakat - Reza Oktavia; Iwan Permana; Liza Dzulhijjah (UNISBA Press, 2024)
Abstract. The proposal is to analyze the validity of QRIS as a means of collecting zakat funds according to Islamic law and Law Number 23 of 2011 concerning Zakat Management. This research uses a normative-empirical approach. The data source used in this study is secondary data and then supported by primary data. The data collection used in this study uses interviews, observations and literature studies. The results of the study show that the practice of paying zakat is carried out by scanning the QR Code, filling in personal data and the number of people, then entering the PIN. The implementation of zakat using QRIS is supervised by the Sharia Supervisory Board and carried out in accordance with the SOPs that have been determined, so as to avoid usury. Based on Islamic law, the use of QRIS as a means of paying zakat is legal because it has fulfilled the pillars and conditions, namely the intention, the existence of muzaki, the existence of mustahik, and the existence of assets issued. Although ijab qabul is not explicitly mentioned, in practice it still exists even though it is done implicitly. Meanwhile, according to the law, the use of QRIS in Indonesia is allowed even though it has not been specifically regulated in the Zakat Management Law, but the use of QRIS has been regulated in the Regulation of Members of the Board of Governors Number 21/18/PADG/2019 concerning the Implementation of the National Standard Quick Response Code for Payments and the use of QRIS has also been allowed by the Financial Services Authority Regulation (PJOK). Therefore, the Zakat Management Law will automatically adjust to the regulations that have been determined at this time. Abstrak. Penelitian ini bertujuan untuk menganalisis keabsahan QRIS sebagai sarana penghimpunan dana zakat menurut hukum islam dan Undang-Undang Nomor 23 Tahun 2011 tentang Pengelola Zakat. Sumber data yang digunakan dalam penelitian ini yaitu data sekunder lalu didukung dengan data primer. Pengumpulan data yang digunakan dalam penelitian ini menggunakan wawancara, observasi dan studi pustaka. Hasil penelitian menunjukan bahwa praktik pembayaran zakat dilakukan dengan cara memindai Code QR, mengisi data diri dan jumlah jiwa, lalu memasukkan PIN. Pelaksanaan zakat menggunakan QRIS ini diawasi oleh Dewan Pengawas Syariah dan dilakukan sesuai dengan SOP yang telah ditentukan, sehingga terhindar dari riba. Berdasarkan hukum Islam penggunaan QRIS sebagai sarana pembayaran zakat itu sah karena telah memenuhi rukun dan syarat, yaitu niat, adanya muzaki, adanya mustahik, serta adanya harta yang dikeluarkan. Meskipun ijab qabul tidak disebutkan secara jelas, namun dalam praktiknya tetap ada meskipun dilakukan secara tersirat. Sedangkan menurut Undang-Undang, penggunaan QRIS di Indonesia diperbolehkan walaupun dalam UU Pengelolaan Zakat belum diatur secara spesifik, namun penggunaan QRIS telah diatur di dalam Peraturan Anggota Dewan Gubernur Nomor 21/18/PADG/2019 tentang Implementasi Standar Nasional Quick Response Code untuk Pembayaran dan penggunaan QRIS juga telah diperbolehkan oleh Peraturan Otoritas Jasa Keuangan (PJOK). Oleh karena itu, UU Pengelolaan Zakat otomatis akan ikut menyesuaikan dengan adanya peraturan yang telah ditentukan pada saat ini.